Capital management in mutual financial institutions - Brown, Christine; Davis, Kevin (Journal of Banking & Finance, 2009)
Capital management by mutual financial institutions (such as credit unions) provides a valuable testing ground for assessing the impact of capital regulation and theories of managerial behaviour in financial institutions. Limited access to external equity capital means that capital accumulation must be met primarily by reliance on retained earnings. To deal with shocks to the capital position and avoid breaching regulatory requirements, managers will aim to have a buffer of capital in excess of the regulatory minimum. Moreover, mutual governance arrangements and an absence of capital market discipline mean that managers have discretion to set target capital ratios which differ significantly from industry averages. This paper develops a formal model of capital management and risk management in mutual financial institutions such as credit unions which reflects these industry characteristics. The model is tested using data from larger credit unions in Australia, which have been subject to the Basel Accord Risk Weighted Capital Requirements since 1993. The data supports the hypothesis that credit unions manage their capital position by setting a short term target profit rate (return on assets) which is positively related to asset growth and which is aimed at gradually removing discrepancies between the actual and desired capital ratio. Desired capital ratios vary significantly across credit unions. There is little evidence of short run adjustments to the risk of the asset portfolio to achieve a desired capital position.